How to Measure the Non-Measurable – The Design of a Tool for Studying the Organizational Culture of Businesses Operating in the Era of Industry 4.0 - Katarzyna Szymańska (Communications of International Proceedings, 2021)
The purpose of the article is to draw attention to the role of organizational culture in the process of implementing the assumptions of the IR 4.0 era. Efforts have been made to design a tool that will support the study of organizational cultures of enterprises operating in the IR 4.0 era by identifying the four main dimensions of such cultures. For this purpose, empirical research was carried out using the author's research tool. It seems that, first, the suggested model of organizational culture of businesses operating in the IR 4.0 era, consisting of the four dimensions described, and, second, the tool designed to study them, are interesting supplements to this research. Furthermore, the dimensions described here, together with their characteristics, form a framework that helps to combine those cultural values that support the development of businesses in the IR 4.0 era. However, it should be noted that the model and the proposed research tool are one proposal that is open to further supplementation with other relevant factors. For practitioners, this article contains a very important and clear message: a properly designed organizational culture of a business can be a real asset for companies, regardless of their size, industry, and location.
Keywords: Organizational culture; open organizational culture; cultural profile in the IR 4.0; era Industry 4.0.